(untitled) (Global Journal of Management and Business Research, 2020)
The ability of a government to ensure an effective and efficient social service delivery is central to good governance. Online platform has become a veritable path to effective and efficient public service delivery globally. The paper investigated the effectiveness and efficiency of online public service delivery in Nigeria from the end-users#x2019; perspective. Using an online survey conducted with online users of services of selected federal agencies in Nigeria, the paper found that online public service delivery in the country was considered effective and efficient, especially when compared with the old physical delivery mode. However, findings further revealed that there was much room for improvement,